Outcomes in patients with acute myocardial infarction and history of illicit drug use: a French nationwide analysis. Issue 9 (28th August 2021) - Ma, Iris; Genet, Thibaud; Clementy, Nicolas; Bisson, Arnaud; Herbert, Julien; Semaan, Carl; Bouteau, Jérémie; Angoulvant, Denis; Ivanes, Fabrice; Fauchier, Laurent
Abstract: Aims : Several reports suggest that illicit drug use may be a major cause of acute myocardial infarction (AMI) independently of smoking habits and associated with a poorer prognosis. The aim of our study was to evaluate the impact of illicit drug use on (i) the risk of AMI and (ii) its prognosis. Methods and results : This French longitudinal cohort study was based on the administrative hospital-discharge database from the entire population. First, we collected data for all patients admitted in hospital in 2013 with at least 5 years of follow-up to identify potential predictors of AMI. In a second phase, we collected data for all patients admitted with AMI from January 2010 to December 2018. We identified patients with a history of illicit drug use (cannabis, cocaine, or opioid). These patients were matched with patients without illicit drug use to assess their prognosis. In 2013, 3 381 472 patients were hospitalized with a mean follow-up of 4.7 ± 1.8 years. In multivariable analysis, among all drugs under evaluation, only cannabis use was significantly associated with a higher risk of AMI [HR 1.32 (95% CI 1.09–1.59), P = 0.004]. Between January 2010 and December 2018, we then identified 738 899 AMI patients. Among these patients, 3827 (0.5%) had a known history of illicit drug use. These patients were younger, most often male and had less comorbidities. After 1:1 propensity score matching, during a mean follow-up of 1.9 ± 2.3 years, there was no significant difference between patients without illicit drug use and patients with illicit drug use regarding all-cause death, cardiovascular death, stroke, or heart failure. Conclusion : In a large and systematic nationwide analysis, cannabis use was an independent risk factor for the incidence of AMI. However, the prognosis of illicit drug users presenting with AMI was similar to patients without illicit drug use.